Is there a role of angiotensin-converting enzyme gene polymorphism in the failure of arteriovenous femoral shunts for hemodialysis? - (:unkn) unknown (ELSEVIER SCIENCE INC, 2001)
In humans, thrombosis and neointimal hyperplasia are the major factors responsible for prosthetic graft occlusion. Previous studies suggest that the renin-angiotensin system is one of the key enzymes in the vascular system and has been implicated in the pathogenesis of thrombosis and neointimal hyperplasia. We conducted a case-control study to determine the frequency of the different angiotensin-converting enzyme (ACE) genotypes among the patients who had PTFE graft implantation for hemodialysis access. Between 1997 and 1999, 30 graft implantations were performed. Twelve individuals (40%) developed thrombotic complications, 8 of the 12 patients had ACE ID polymorphism, and 2 patients had DD and 2 patients had II polymorphism. The ID polymorphism was significantly more frequent in the thrombosed arteriovenous (A-V) grafts than in nonthrombosed A-V grafts (chi (2) = 7.57 and p = 0.02). Overall, the frequency of the D and I alleles was 66.6 and 33.3%, respectively. In conclusion, ID polymorphism of the ACE gene plays an important role in the pathogenesis of vascular access thrombosis in subjects undergoing hemodialysis for chronic renal failure.
Keywords: DELETION POLYMORPHISM; RISK-FACTOR; RESTENOSIS; THROMBOSIS; CELLS; GENOTYPE; DISEASE